32 is the answer to the problem
Answer:
D
Step-by-step explanation:
since it's a multiplication consider the two factors one by one
cubic root of y^6 = y^(6/3) = y^2
cubic root of 8x^3= 2x^(3/3)= 2x
so 2xy^2
Answer:
![x=-3+\sqrt{27}\\ x=-3-\sqrt{27}](https://tex.z-dn.net/?f=x%3D-3%2B%5Csqrt%7B27%7D%5C%5C%20%20x%3D-3-%5Csqrt%7B27%7D)
Step-by-step explanation:
Let's find our C value for the quadratic equation.
![(\frac{6}{2})^{2} = 9](https://tex.z-dn.net/?f=%28%5Cfrac%7B6%7D%7B2%7D%29%5E%7B2%7D%20%3D%209)
That is our C. Since we added 9 to one side, we have to do the same to the other. We get:
![x^{2} +6x + 9 = 18 + 9\\x^{2} +6x + 9 = 27](https://tex.z-dn.net/?f=x%5E%7B2%7D%20%2B6x%20%2B%209%20%3D%2018%20%2B%209%5C%5Cx%5E%7B2%7D%20%2B6x%20%2B%209%20%3D%2027)
Now, lets form the left side as a binomial squared.
![(x+3)^{2} = 27](https://tex.z-dn.net/?f=%28x%2B3%29%5E%7B2%7D%20%3D%2027)
Let's square both sides now:
![x+3 = (+/-)\sqrt{27}](https://tex.z-dn.net/?f=x%2B3%20%3D%20%28%2B%2F-%29%5Csqrt%7B27%7D)
Now, we subtract 3 from both sides to isolate the variable, X:
![x= -3(+/-)\sqrt{27}](https://tex.z-dn.net/?f=x%3D%20-3%28%2B%2F-%29%5Csqrt%7B27%7D)
This means that the answers are:
![x=-3+\sqrt{27}\\ x=-3-\sqrt{27}](https://tex.z-dn.net/?f=x%3D-3%2B%5Csqrt%7B27%7D%5C%5C%20%20x%3D-3-%5Csqrt%7B27%7D)
I do not understand your answers though. Answer A makes no sense, answer B is 221, answer C is 115, and answer D also does not make sense. If you could clarify this portion, maybe I can help you find your alphabetic answer